2015
DOI: 10.17675/2305-6894-2015-4-1-125-138
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between cationic polyethyleneimine and anionic polyelectrolytes for the control of silica scale formation in process waters

Abstract: Stabilization of mono-and disilicic acids is accomplished by using a cationic polymeric chemical additive, polyethyleneimine (PEI), in supersaturated silica solutions (the starting solution contained 500 ppm/8.3 mM sodium orthosilicate, Na 2 SiO 3 ·5H 2 O, expressed as SiO 2 ) at pH = 7. The PEI polymeric system contains an excess of amine groups (~25% primary amines, ~50% secondary amines and ~25% tertiary amines) that become protonated at circumneutral pH, hence charging the molecules positively. PEI was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Demadis et al reported that phosphonated chitosan ( PCH ) can be used as an inhibitor of silicic acid polycondensation, but there appear to be no reports on calcite or barite inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Demadis et al reported that phosphonated chitosan ( PCH ) can be used as an inhibitor of silicic acid polycondensation, but there appear to be no reports on calcite or barite inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the influence of long-chain polyamines isolated from diatom cell walls on silica precipitation in vitro , , inspiring the exploration of synthetic organic macromolecules as inhibitors of silica polymerization. Examples of such polymeric inhibitors include neutral polymers, e.g., poly­(ethylene oxide) and polyvinylpyrrolidone, and cationic polyelectrolytes such as protonated polyaminoamide dendrimers , and polyethylenimines . However, the limited number of comprehensive studies on these polymeric silica inhibitors has resulted in a lack of consensus regarding the governing mechanisms behind the stabilization of reactive silicic acid species.…”
Section: Introductionmentioning
confidence: 99%
“…The silicic acid polycondensation process and the physicochemical factors that influence it have been part of on-going investigations in our laboratory. The goal is to prevent silica formation, by stabilizing silicic acid, through the discovery and application of chemical scale inhibitors and additives [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%